Active-marker systems and future directions in 3D movement analysis - Mitchelson, D. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
Evolution of Codamotion • Focus on the sensor technology - What paradigms exist for optical movement measurement? - Introduction to mask-correlation techniques - How do these compare with photogrammetry/ vision-based methods? • Applications of the Codamotion Technology